Combined Effects of Atmospheric and Seafloor Iron Fluxes to the Glacial Ocean. (11th November 2017) - Muglia, Juan; Somes, Christopher J.; Nickelsen, Levin; Schmittner, Andreas
Abstract: Changes in the ocean iron cycle could help explain the low atmospheric CO2 during the Last Glacial Maximum (LGM). Previous modeling studies have mostly considered changes in aeolian iron fluxes, although it is known that sedimentary and hydrothermal fluxes are important iron sources for today's ocean. Here we explore effects of preindustrial‐to‐LGM changes in atmospheric dust, sedimentary, and hydrothermal fluxes on the ocean's iron and carbon cycles in a global coupled biogeochemical‐circulation model. Considering variable atmospheric iron solubility decreases LGM surface soluble iron fluxes compared with assuming constant solubility. This limits potential increases in productivity and export production due to surface iron fertilization, lowering atmospheric CO2 by only 4 ppm. The effect is countered by a decrease in sedimentary flux due to lower sea level, which increases CO2 by 15 ppm. Assuming a 10 times higher iron dust solubility in the Southern Ocean, combined with changes in sedimentary flux, we obtain an atmospheric CO2 reduction of 13 ppm. The high uncertainty in the iron fluxes does not allow us to determine the net direction and magnitude of variations in atmospheric CO2 due to changes in the iron cycle. Our model does not account for changes to iron‐binding ligand concentrations that could modify the results. We conclude that when evaluating glacial‐interglacial changes in the ocean iron cycle, not only surface but also seafloor fluxes must be taken into account. Plain Language Summary: During cold climate periods such as the Last Glacial Maximum (LGM, approximately 20 thousand years before present), ice sheets occupied most of North America and Europe, producing lower sea level than in modern times, and atmospheric carbon was also lower than today. One mechanism proposed to link low atmospheric carbon to glacial periods is an increase in the sinking of organic carbon from the surface Southern Ocean and its accumulation in deep waters. This could have happened through iron, an important nutrient for phytoplankton production that is mostly missing in that region. If iron levels were higher in the LGM, then more phytoplankton would grow, sequestering carbon from the atmosphere, and sinking it to deep waters as dead matter. In this work we use a climate model to study differences between the iron cycles of preindustrial times and the LGM. We find that an increase of atmospheric dust flux to the ocean raised ocean iron in the LGM's Southern Ocean, increasing productivity and sinking sequestered atmospheric carbon as organic matter. However, we also find that lower sea level in the LGM exposed continental shelves, decreasing the iron flux coming from marine sediments, acting against the other effect. Key Points: Effects from dust, sedimentary, and hydrothermal fluxes on glacial iron and carbon are explored Higher dust iron flux may have been opposed by reduced sedimentary iron flux due to sea level drop The impact on CO2 is uncertain, ranging from +15 to −28 ppm depending on the mechanisms considered